YouTube as an Alternative Media for Teaching Speaking in Online Class during COVID-19 Pandemic - Saadillah Saadillah; Muhammad Sam Bahri; Nor Izzatil Hasanah (UMBanjarmasin, 2022)
The Covid-19 pandemic has spread worldwide, significantly disrupting the education sector which is the focus of this research. They have to study independently at home to prevent catching diseases commonly spread by Covid-19 students. The usage of online learning is a technique that enables learning activities to go on without interruption; this is evident when learning occurs in the grade 10th of the language department in teaching English at MAN Kotawaringin Timur, When the learning process is continuing, both students and subject teachers feel very helped. Based on the phenomena above, researchers are interested in assessing the use of YouTube as an alternative medium for online learning using a qualitative descriptive method. This method would include data collection strategies, data conversion techniques, data sharing procedures, and data interpretation techniques. The findings of this research suggest that students can benefit from using YouTube as an alternate media for online-based learning while the COVID-19 epidemic is ongoing. YouTube is a medium that can help students comprehend English language instruction at MAN. Kotawaringin Timur.